PENERAPAN METODE VISUAL AUDITORY DALAM PENINGKATAN KEBERHASILAN TOILET TRAINING PADA ANAK PRASEKOLAH - Lilis Maghfuroh (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Toilet training or training for bowel and bladder is a major task in preschoolers. Since the percentage preschoolers who use diapres in RA Perwanida 3 Sukoanyar Turi, it proves that the children has not succeeded in toilet training. This study aims to determine the effect of visual auditory on toilet training in preschoolers. The design used "Pre-Experimental" (One-group pretest-posttest design), population was 55 children with a sample of 49 children using taken simple random sampling by the Wilcoxon test. Data collection used questionnaires confirmed in the form of percentage and narrative. The results obtained Z = -2.887 with significant p = 0.004 where (p <0.05). So was accepted meaning that there is a visual auditory influence on toilet training in preschoolers. This study can provide input for parents to teach toilet training with visual auditory so that children can understand more easily and have interest.